PENGARUH LITERASI KEUANGAN, KEPRIBADIAN DAN PERBEDAAN GENDER TERHADAP PERENCANAAN KEUANGAN KELUARGA DI POLITEKNIK PELAYARAN SURABAYA - Rizky Indra Pradita (Behavioral Accounting Journal, 2021)
This research is to gain an understanding, to test, and to prove the influence of financial literacy, personality and gender differences on family financial planning. This study applies a "quantitative approach". The information obtained in this study uses “primary data” collected through a questionnaire survey. The sample in this study was "Surabaya Polytechnic Employees". Sample selection using incidental sampling method. Data analysis used validity test, reliability test and multiple linear regression with SPSS 23 application. The findings showed that financial literacy partially had a negative effect on Family Financial Planning at the Surabaya Shipping Polytechnic. Personality and gender differences partially have a positive effect on Family Financial Planning at the Surabaya Shipping Polytechnic. Simultaneously there is an influence of financial literacy, personality and gender differences on family financial planning at the Surabaya Shipping Polytechnic. Keywords: financial literacy, personality, gender differences, family financial planning